Improving stakeholder participation in schools: Intentionally inviting practices of school heads in Cape Coast and Ajumako school districts, Ghana - Amakyi, Michael; Ampah-Mensah, Alfred; Bakah, Marie Baah (Advances in Social Sciences Research Journal, 2022)
A sequential mixed-method design adopting a non-experimental survey and a basic interpretive study was used to explore the intentionally inviting practices of school heads of the Cape Coast metropolis and Ajumako district. Data were collected using 2 X 2 Intentionally-Inviting Matrix and semi-structured interview protocols. Data collected from the survey were analysed using frequency counts, while the data from the interview were analyzed and put into themes that provided a description on how the adopted practices promote stakeholder participation. The study findings revealed that school heads in Cape Coast metropolis and Ajumako district adopt intentionally inviting practices that address the physical frame of the school, communication with stakeholders, and building relationship with stakeholders to promote stakeholder involvement in schools. The study further revealed that the adopted practices of the school heads foster a sense of pride in the stakeholders to be connected to the school. The practices also increase stakeholder confidence and trust in the school head. The Ghana Education Service should replicate the study in other school districts to identify the practices that support stakeholder participation in schools and also conduct a similar study to elicit the perceptions of stakeholders on practices that enhance their participation in schools.